Incorporation of oligo(β-pinene) in poly(vinyl alcohol)-chitosan scaffolds: a strategy to improving biocompatibility - Rodrigues, Plínio Ribeiro; de Castro, Karine Cappuccio [UNESP]; Vicente, Cristina Pontes; Mei, Lucia Helena Innocentini; Vieira, Roniérik Pioli (Springer Nature, 2024)
Bioactive compounds blended with synthetic polymers constitute an effective alternative for tailored materials design in advanced applications. Biological functionalities are easily incorporated, and the materials’ overall performance can be improved using this technique. The present work introduces the production and characterization of electrospun scaffolds comprised poly(vinyl alcohol), chitosan, and oligo(β-pinene) with potential for tissue engineering. Oligo(β-pinene) presents many biological functionalities of interest, especially cytoprotective activity. The scaffolds’ structure, processing, properties, and performance relationships were evaluated. The materials presented an average fiber diameter of 159 nm, which was increased with the oligo(β-pinene) addition in the polymer matrix. There was an overall trend of crystallinity decrease (from 21.02 to 6.4%) with the incorporation of the oligomer. The polymers’ ∆Hm and Tm increased from 28.43 to 35.51 J g−1 and from 190.54 to 194.10 °C, respectively, with the addition of oligo(β-pinene). The presence of a few fiber defects appeared upon oligomer inclusion. However, the overall thermal performance of the scaffolds improved with the increase in oligo(β-pinene) content on the nanofibers. Essays of cell proliferation revealed significant benefits from oligo(β-pinene) inclusion on the blends tested. Biocompatibility improvement of up to 21.5% was noted compared to the control. Thus, incorporating oligo(β-pinene) in poly(vinyl alcohol)-chitosan electrospun nanofibers constitutes a renewable option to enhance the scaffolds’ properties and biocompatibility.
Keywords: Biopolymer; Blends; Electrospinning; Nanofibers; O-ATRP; Tissue engineering